Exploring Shopper Insights of Social Media Use in Saudi Arabia - Mohammad Zulfeequar Alam (International Review of Management and Marketing, 2017)
Social media inspired millions of users from all over the world. This media has made the connection more familiar to ones that are more intelligent. This new medium of communication wins the trust of consumers by connecting with them at a deeper level. Global and local companies have recognized social media marketing as a potential marketing platform and have utilized with innovations to power their advertising campaign their marketing approach through social media. One cannot afford to not having any presence on the social network channel now a day when their counterparts are having waves of products and services in the market. Despite, the spread of social media and the broad adoption of these various communication tools, there is a lack of studies in Saudi region that conceptualized the goals of objectives of the study. A convenience sample survey has been collected from 226 respondents through using the online survey via Google forms & monkey survey during three months from October to December 2015. The close-ended questionnaire was used, and particular care has been taken to reduce the non-response rate and the error arising out of it. After collecting the data, it was manually edited, coded and then recorded on excel sheet. For descriptive analysis statistics (frequency distribution), Chi-square goodness of fitness test at P. Value 0.05 was applied, and result findings were interpreted accordingly in the study.